The Transformative Potential of Black British and British Muslim Literature: Heterotopic Spaces and the Politics of Destabilisation - Ahrens, Lisa (transcript, 2019)
This study investigates power, belonging and exclusion in British society by analysing representations of the mosque, the University of Oxford, and the plantation in novels by Leila Aboulela, Robin Yassin-Kassab, Diran Adebayo, David Dabydeen, Andrea Levy, and Bernardine Evaristo.Lisa Ahrens combines Foucault's theory of heterotopia with elements of Wolfgang Iser's reader-response theory to work out Black British and British Muslim literature's potential for destabilising exclusionary boundaries. In this way, new perspectives open up on the intersections between space, power and literature, intertwining and enriching the discourses of Cultural and Literary Studies.